Eksplorasi Bakteri Indigen pada Pembenihan Ikan Lele Dumbo (Clarias sp.) Sistem Resirkulasi Tertutup [Exploration Of Indigen Bacteria From Catfish (Clarias sp.) Breeding On Closed Resirculation System ] - Prayogo Prayogo; Boedi Setya Rahardja; Abdul Manan (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract The efforts of the catfish hatchery fish are generally confined to the central areas of hatchery that has abundant water resources. Solving the problem of limited water, appears a catfish hatchery system with a closed recirculation system. In such systems the process of biological filtration is the most important thing. It shows the handling of organic materials by utilizing the degrading bacteria is the key to successful management of the system. Thus necessary to be studied the role of bacteria degrading organic matter indigen (local bacteria) in the closed hatchery recirculation system of catfish. This study aimed to obtain bacterial strains degrading bacteria indigen as organic materials are very useful in improving water quality in the closed hatchery recirculation system of catfish and knowing the methods to the use of bacteria indigen as degrading organic matter. The method used in this study was designed based on the stages of research carried out in accordance with the objectives to be achieved. The results of the isolation and identification to the species level showed Pseudomonas stutzeri and Pseudomonas pseudomallei obtain the greatest value for hydrolysis index representing each trait protease, lipase and amylase. Bioremediation effectiveness test in vitro showed effective results in the treatment using consortia of bacteria inoculant. Consortia of bacteria inoculant effective in improving the growth rate and survival rate (SR) in the closed hatchery recirculation system of catfish.